Initial growth of Schizolobium parahybae in Brazilian Cerrado soil under liming and mineral fertilization - Coneglian, Ademilson; Ribeiro, Pedro H. P.; Melo, Bruno S.; Pereira, Rennan F.; Dorneles Junior, Joaz [UNESP] (Univ Federal Campina Grande, 2016)
High prices and the scarcity of hardwoods require the use of alternative wood sources, such as the Guapuruvu (Schizolobium parahybae), an arboreal species native to the Atlantic Forest, which has fast growth and high market potential. However, there is no information on its cultivation in the Brazilian Cerrado. Thus, this study aimed to analyze the contribution of mineral fertilization and liming in a Cerrado soil on the initial growth of Schizolobium parahybae. The experiment was set in a randomized block design, with 4 treatments (Cerrado soil; soil + liming; soil + fertilizer; and soil + fertilizer + liming) and 15 replicates. The following variables were analyzed: plant height, stem diameter, number of leaves, total, shoot, leaf, root and stem dry matter, and root/shoot ratio. The obtained data were subjected to the analysis of variance, Tukey test and regression analysis. During the initial growth, Schizolobium parahybae can be cultivated in a Brazilian Cerrado soil only under mineral fertilization, with no need for soil liming.
Keywords: Guapuruvu; native species; timber potential